Global Diversification, Growth, and Welfare with Imperfectly Integrated Markets for Goods - Dumas, Bernard; Uppal, R (Review of Financial Studies, 2001)
In this article we examine the effect of the imperfect mobility of goods on international risk sharing and, through that, on the investment in risky projects, welfare, and growth. Our main result is that the welfare gain from integration of financial markets is not greatly reduced by the presence of goods market imperfections, modeled as a cost of transferring goods from one country to the other. We also find that the gain is nonmonotonic with respect to investors' risk aversion and the aggregate volatility of output growth. The policy implication to be drawn is that financial market integration is a worthwhile goal to pursue even when full goods mobility has not been achieved. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.